2015
DOI: 10.1002/joc.4304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the North Atlantic Oscillation on the Dipole Oscillation of summer precipitation over the central and eastern Tibetan Plateau

Abstract: An analysis of the spatiotemporal variability in summer precipitation during the period 1961-2010 is presented based on monthly precipitation datasets from 66 meteorological stations in the central and eastern Tibetan Plateau (TP). By applying empirical orthogonal function (EOF) analysis, a strong reversal is found in the variability of summer precipitation between the northeastern and the southeastern TP on the inter-annual timescale; this reversal is defined as the Dipole Oscillation in summer precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 53 publications
3
65
0
Order By: Relevance
“…Precipitation is a major factor in drought occurrence. Previous studies indicated that atmospheric circulations including Asian summer monsoon and NAO have profound effects on precipitation in China [31][32][33][34]. In order to explore the relationships between atmospheric circulation and drought variation in Ningxia, the Pearson's correlation analysis was applied.…”
Section: Potential Causal Factors For Drought Variation In Ningxiamentioning
confidence: 99%
See 4 more Smart Citations
“…Precipitation is a major factor in drought occurrence. Previous studies indicated that atmospheric circulations including Asian summer monsoon and NAO have profound effects on precipitation in China [31][32][33][34]. In order to explore the relationships between atmospheric circulation and drought variation in Ningxia, the Pearson's correlation analysis was applied.…”
Section: Potential Causal Factors For Drought Variation In Ningxiamentioning
confidence: 99%
“…This shows that drought variation for summer in Ningxia is likely to be related to the NAO over the last 40 years. Previous studies discovered that the summer precipitation over the eastern Tibetan Plateau (TP) is closely associated with the NAO [33,34]. The NAO primarily modifies the upper-level atmosphere [34].…”
Section: Potential Causal Factors For Drought Variation In Ningxiamentioning
confidence: 99%
See 3 more Smart Citations